Psychosocial factors of patients with venous leg ulcers and their association with healing - Cifuentes Rodriguez, Johana Enyd; Guerrero Gamboa, Sandra (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objectives: To identify psychosocial factors present in patients with venous leg ulcers and the association that these factors have in the healing of venous leg ulcers. Methods: An integrative review of the quantitative studies in MEDLINE, Scielo and Cochrane Library databases, between 2008 and 2019, using the keywords, psychosocial factors, venous ulcer, wound healing, anxiety and depression in English, Spanish and Portuguese. Results: sixteen studies were included. The psychosocial factors present in patients with venous ulcers were depression, anxiety, feelings of helplessness, subjective well-being, self-esteem, loneliness and spirituality. Stress, a negative perception of venous ulcer, living alone and severe experience of symptoms such as pain and depression have statistically significant associations with longer periods of healing. Conclusions: Depression is one of the most frequently measured factors and present in this population. The available evidence on the association of psychosocial factors with the healing of venous ulcers is low.